Imaging changes following surgery for ischiofemoral impingement. Issue 3 (4th May 2023) - Hatem, Munif; Feng, Richard; Teel, Jordan; Martin, Hal David
Abstract: Partial resection of the lesser trochanter (LT plasty) has been increasingly recommended to treat ischiofemoral impingement. However, there is a lack of studies on the imaging findings following LT plasty. The purpose of this study was to assess magnetic resonance imaging (MRI) changes on the lesser trochanter and surrounding musculotendinous structures following LT plasty to treat ischiofemoral impingement. Twenty-one patients (21 hips) were studied. The LT length and cross-sectional area of the iliopsoas muscle were measured on MRI before and after surgery. The MRIs were performed on average 11 months (range, 3 to 25 months) after surgery. The mean ±  standard deviation amount of LT resected (difference between pre- and postoperative LT length) was 7.3 mm ±  2.5 mm. The iliopsoas cross-sectional area decreased after the LT plasty in 95% of the hips (20/21) by an average of 35% ± 16%. The reduction in iliopsoas size had no significant correlation with improvement on the modified Harris Hip Score at a mean follow-up of 17 months after surgery (r = −0.13, P  = 0.58). The iliopsoas muscle size decreased on average 35% following endoscopic LT plasty. The decrease was not correlated with midterm functional outcomes.